The Super Clean-Up Game: Adapting a Traditional Behavioral Engagement Technique to Promote Productivity and Peer Cohesion Among Youth with Autism Spectrum Disorder - Miller, Zoe M. (Tufts Archival Research Center, 2020)
The Good Behavior Game is a behavioral management technique typically used in traditional classroom settings. This study tested the effectiveness of a modified version of the GBG for youth with Autism Spectrum Disorder (ASD). The Super Clean-Up Game was developed with the intent to 1. create an inclusive behavioral management technique that works for youth both with and without ASD; and 2. create a behavioral management technique that can be used to increase productivity and strengthen the social skills of youth with ASD. The Super Clean-Up Game was implemented at a residential summer camp for youth with social, emotional, and behavioral challenges, with four bunks of campers (N = 24, 100% boys, ages 11-16 years-old). The rate of campers’ on-task and helping behaviors were measured, as well as the number of chores completed by campers. There was an increase in the rate of on-task, chore-related, and helping behaviors between the initial baseline and intervention phases in all four bunks. Results provide preliminary evidence that the Super Clean-Up Game is an effective behavior management technique and social skills intervention for youth with ASD. Future studies may consider modifying the Super Clean-Up Game for use with youth with ASD in other contexts, such as classrooms.; Advisor: Dr. Eileen Crehan